(untitled) (Fiep Bulletin - online, 2013)
Under the holistic perspective of Traditional Chinese Medicine (TCM), we believe that the anxiety, fear, sadness, anger and/or pain case psychosomatics imbalance in humans being responsible for symptoms of discomfort causing the decrease in quality of life. Acupuncture is a treatment of the TCM, accessible and with the response time minimum for obtaining relief or cure of symptoms, especially without the use of medications. In this sense, therapy used takes into account habits of life, poles Yin and Yang, strength of life, constituent elements of each person, personal and family history. The anamneses collected aims to diagnose patterns of disharmony as deficiency, excess, stagnant, cold, heat, internal and external. The purpose of the survey was to check the response of the TCM intervention in the treatment of neck pain of a dancer of 52 years old attended by nurses during a stage of training in acupuncture. We diagnosed as the original question Qi stagnation and advancement Yang of the liver taking wood as a trainer element of the patient. We chose key points for obtaining relief from pain and balance the energy flow in patients to know: EX-HN3, LI4, TH5, GB21, GB34, GB41, LR3, BL17, BL40, BL43, BL57, BL60, BL62, K6, DM9, DM14, and DM20. The meetings took place once a week, applying needles and electro acupuncture in points in the posterior anatomical position, in pairs sessions. After 6 episodes of treatment, the painful discomfort and use of cervical collar were eliminated. Thus, we can see the effectiveness of the treatment of neck pain by intervention of TCM considering the bio-psycho-emotional context of the patient for the selection of acupuncture’s points.